Comparative evaluation of the shear bond strength of adhesive and self-adhesive resin luting agents to three commercially available composite core build-up materials: An in vitro study - Prachiti M Terni; Jyoti B Nadgere; Sabita M Ram; Naisargi P Shah; Janani Mahadevan (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of the study was to evaluate the shear bond strength of adhesive and self-adhesive resin luting agents (RLAs) to three commercially available composite core build-up materials (CBMs). Settings and Design: Comparative -invitro study. Materials and Methods: Sixty samples, 20 each of self-cure (Incore, Medicept: Group I), light cure (Light-Core, Bisco: Group II), and dual cure (LuxaCore Z-Dual, DMG America: Group III) composite CBMs were made in the lower mold space of a customized stainless steel jig. They were further subdivided into subgroups A and B for bonding with the adhesive (RelyX Ultimate, 3M ESPE) and self-adhesive (RelyX Unicem, 3M ESPE) RLAs respectively. For specimens in subgroup A, the bonding agent (Scotchbond Universal Adhesive, 3M ESPE) was rubbed onto the surface for 20 s prior to bonding with the adhesive RLA. For specimens in subgroup B, no pretreatment of the surface was carried out. The CBM-luting agent sample was tested for the shear bond strength in a universal testing machine. Statistical Analysis Used: ANOVA, Tukey's multiple comparison, and independent t-test. Results: Adhesive RLA showed the highest shear bond strength to light cured composite CBM. Self-adhesive RLA showed the highest shear bond strength to dual-cured composite CBM. Adhesive RLA showed higher shear bond strength to all three composite CBMs as compared to the self-adhesive luting agent. This difference was statistically significant for the self-cure and light cure composite CBMs. Conclusion: Adhesive RLA showed greater shear bond strengths to all the three groups of composite CBMs as compared to self-adhesive RLA.